Wykonaj działania :
b) ( 3x - 2)( 3x - 2y + 1) - 4x ( 2x - 3y + 1)
c) 2 ( m + 1) ( n - 2) + 2 ( n +1) ( m - 2)
d) x ( x + 1) ( x + 2) - x ( x -1) ( x - 2)


Zapisz w postaci sumy algebraicznej :

b) ( x - 2) ( x + 5) ( 2x - 1)
d) ( 2x - 3) kwadrat ( x +2)

3

Odpowiedzi

Najlepsza Odpowiedź!
2009-11-14T17:22:22+01:00
B) ( 3x - 2)( 3x - 2y + 1) - 4x ( 2x - 3y + 1) =
=9x²-6xy +3x - 6x+4y -2 - 8x² +12xy - 4x =
x² +6xy-7x +4y - 2

c) 2 ( m + 1) ( n - 2) + 2 ( n +1) ( m - 2) =
=2(mn - 2m + n - 2) + 2( mn - 2n + m - 2)
=2mn -4m +2n -4 + 2mn -4n +2m -4 =
=4mn- 2m- 2n - 8

d) x ( x + 1) ( x + 2) - x ( x -1) ( x - 2)=
= x(x²+2) - x(x²+2) =
x³+ 2x -x³ - 2x = 0


Zapisz w postaci sumy algebraicznej :

b) ( x - 2) ( x + 5) ( 2x - 1) =
=(x² - 10) (2x - 1) = 2x³ +10

d) ( 2x - 3) ² ( x +2) =
(4x² - 12x + 9) (x +2) =
4x³ +8x² - 12x² - 24x +9x +18 =
4x³ - 4x² - 15x +18
2 5 2
2009-11-14T17:28:11+01:00
B) 9x²-6xy+3x-6x+4y-2-8x²+12xy-4x=x²-7x+6xy+4y-2

c) 2(mn-2m+n-2)+ 2(nm-2n+m-2)=2mn-4m+2n-4+2mn-4n+2m-4= 4mn-2m-2n-8

d) d) x ( x + 1) ( x + 2) - x ( x -1) ( x - 2)=
= x(x²+2) - x(x²+2) =x³+ 2x -x³ - 2x = 0
22 4 22
2009-11-14T17:41:25+01:00
B)=9x²-6xy+3x-6x+4y-2-8x²+12xy-4x=x²+6xy-7x+4y-2
c)=2*(mn-2m+n-2)+2(mn-2n+m-2)=2-4m+2n-4+2mn-4n+2m-4=4mn+6m-2n-8
d)=x(x²+2x+x+2)-x(x²-2x-x+2)=x³+2x²+x²+2x-x³+2x²+x²-2x=6x²

b)=(x²+5x-2x-10)*(2x-1)=2x³-x²+10x²-5x-4x²+2x-20x+10=2x³+5x²-23x+10
d)=(4x²-12x+9)*(x+2)=4x³+8x²-12x²-24x+9x+18=4x³-4x²-15x+18
9 4 9